Effectiveness of Providing Complex Food and Formula Milk on the Growth and Development of Children Aged 12-24 Months in 2024 - Nur Anita; Retno Indah Lestari; Rindiani Suryana; Nur Sobah; Siti Munasaroh; Siti Anis; Evita Apriyani; Nunung Yuliah; Ruri Kurniati (Postgraduate, University of Mataram, 2025)
World health organization predicts there is around 149.2 million children under​ 5 year old who experienced disturbance growth and development consequence lack intake nutrition during transition between exclusive breastfeeding , so need adequate understanding and intake​ moment giving food breast milk companion. This study aims to analyze the effectiveness of complementary feeding (MPASI) and formula milk on the growth and development of children aged 12-24 months. A quasi-experimental design was employed with 208 respondents divided into intervention and control groups. Data were collected using structured questionnaires, observation sheets, and the Pre-Screening Developmental Questionnaire (KPSP) to assess child development. Statistical analysis was conducted using chi-square tests and logistic regression with SPSS software. The results indicated a significant relationship between the type of complementary feeding provided and weight gain as well as developmental score improvement (p<0.05). Respondents who received high-protein and micronutrient-rich MPASI exhibited better weight gain compared to the control group. Additionally, children in the intervention group demonstrated a significant increase in KPSP scores, reflecting better developmental progress. In conclusion, providing varied complementary feeding along with formula milk significantly contributes to enhancing the growth and development of children aged 12-24 months. Therefore, parents and healthcare providers should ensure appropriate complementary feeding practices to prevent nutritional deficiencies and stunting in children.